An evaluation of the lung function of eight to twelve year old children living in Table View, Cape Town - W. J. Esterhuyse; S. H. Irwin-Carruthers (AOSIS, 1992)
Two groups of twenty children between the ages of 8 and 12 years, who lived in areas near the petrochemical complex in Table View, were studied to ascertain the prevalence of respiratory disease. A random sample of 15children from each group was subjected to lung function testing using the ELF. Results showed a higher incidence of respiratory disease in the group living closer to the petrochemical complex, but the sample was too small to show any statistical significance. There was no difference in lung function test results between the two groups, but both groups demonstrated lower values than the predicted norms for their age, weight and height.